Do reading boredom and reading boredom coping strategies predict reading comprehension performance? An empirical investigation of Saudi EFL learners - Shehzad, Muhammad Waleed; Ahmed, Rida; Razzaq, Shazma; Akhtar, Amer; Hasan, Md. Kamrul (Universitas Pendidikan Indonesia, 2020)
Boredom is a well-researched concept in various contexts; nonetheless, there is scarceness of research related to the relationship of boredom with reading comprehension performance in EFL context. Therefore, this study intends to determine the connection between reading boredom and reading comprehension performance by employing reading boredom coping strategies as a mediator. A quantitative research approach, and a cross-sectional and correlational research design was employed to conduct this study. Questionnaires and a reading comprehension test were used to collect data from 306 Saudi EFL students. Findings indicated that reading boredom showed a significant but negative relationship with reading comprehension performance. Also, reading boredom was positively and significantly related to reading boredom coping strategies. Moreover, reading boredom coping strategies showed a positive and significant relationship with reading comprehension performance. Lastly, findings indicated that reading boredom coping strategies mediated the association between reading boredom and reading comprehension performance. On the basis of aforementioned findings, numerous recommendations for EFL students, teachers, and policymakers were offered.